On a nonlinear nonlocal model for a population with separate dispersal and sedentary stages. (December 2021) - Deng, Keng; Huang, Qihua
Abstract: The life cycles of many species include separate dispersal and sedentary stages. To understand the population dynamics of such species, we study a hybrid model consisting of a reaction–diffusion equation that governs the random movement and settlement of dispersal individuals and an age-structured hyperbolic equation that describes the growth of sedentary individuals. We establish the existence and uniqueness of the solution of the model using the monotone method based on a comparison principle. We study the population persistence and extirpation by means of three measures. We also verify the theoretical results through numerical simulations.